2017
DOI: 10.18632/oncotarget.18645
|View full text |Cite
|
Sign up to set email alerts
|

Human steroid sulfatase induces Wnt/β-catenin signaling and epithelial-mesenchymal transition by upregulating Twist1 and HIF-1α in human prostate and cervical cancer cells

Abstract: Steroid sulfatase (STS) catalyzes the hydrolysis of estrone sulfate and dehydroepiandrosterone sulfate (DHEAS) to their unconjugated biologically active forms. Although STS is considered a therapeutic target for estrogen-dependent diseases, the cellular functions of STS remain unclear. We found that STS induces Wnt/β-catenin s Delete ignaling in PC-3 and HeLa cells. STS increases levels of β-catenin, phospho-β-catenin, and phospho-GSK3β. Enhanced translocation of β-catenin to the nucleus by STS might activate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…For example, EMT was induced by SET in pancreatic cancer, lung cancer, 32 prostatic carcinoma and cervical cancer. 33 As for CCRCC, it was revealed that EMT was attenuated by miR-138 in CCRCC cells, indicating the tumor suppression function of miR-138. 34 on the contrary, IL-6 induces EMT and stimulates metastasis in CCRCC.…”
Section: Discussionmentioning
confidence: 94%
“…For example, EMT was induced by SET in pancreatic cancer, lung cancer, 32 prostatic carcinoma and cervical cancer. 33 As for CCRCC, it was revealed that EMT was attenuated by miR-138 in CCRCC cells, indicating the tumor suppression function of miR-138. 34 on the contrary, IL-6 induces EMT and stimulates metastasis in CCRCC.…”
Section: Discussionmentioning
confidence: 94%
“…Considering these previous reports and our GSEA results, high expression of SLCO2B1 appears to activate EMT through the upregulation of sonic hedgehog, IL-6/JAK/STAT3 and K-ras signaling pathways. In agreement, DHEA, one of the major metabolites from DHEAS, has been shown to accelerate EMT through E-cadherin suppression and the induction of N-cadherin and Vimentin in PCa [ 34 ]. Taken together, it is possible that high expression of SLCO2B1 accelerates the influx of DHEAS, which is then metabolized to the more active DHEA.…”
Section: Discussionmentioning
confidence: 99%
“…These actions were shown to be through increased estrogen desulfation and activation of the GPER, a finding further supported by evidence these effects may be modulated by a hypoxic environment (Bustos et al 2017). Indeed, it is of interest to note STS activity can increase hypoxia inducible factor HIF1A expression in cervical and prostate cancer cells, suggesting STS action may be further regulated by hypoxic conditions (Shin et al 2017). Furthermore, E 2 treatment increases both STS activity (Gilligan et al 2017a) and GPER expression in CRC (Bustos et al 2017), suggesting a novel positive feedback loop through which E 2 can drive CRC proliferation.…”
Section: Gastrointestinal Cancersmentioning
confidence: 76%